Incidence and antibiotic susceptibility of bacteria in goat milk in Ibadan, Nigeria (2018)
Goat milk and itsproducts are highly nutritious and widely consumed in several countries. In Nigeria, little attention has been given to goats as dairy animals; hence thè raw milk can be a potential source of bacterial contamination and spread of antibiotic resistant pathogens within human, animai and environment. In this study, thè incidence and antibiotic susceptibility of bacteria in goat milk in Ibadan, Nigeria was evaluated. The bacteriological quality and antibiotic resistance characteristics of thè isolates froml05 raw milk samples collectedfrom does in fìve goat herds in Ibadan in Oyo-State, Nigeria were carried out. A total ofl26 bacterial isolates belonging to six bacteria genera [Lactobacillus spp (23.81 %), Staphylococcus aureus (23.02%), E.coli (20.63%), Klebsiella pneumonia (15.08%), Pseudomonas aeruginosa (10.35%), Streptococcus spp (07.14%)] were obtainedfrom thè samples. The Gram negative isolates exhibited resistance to amoxillin (84.50%), augmentin (77.59%), septrìn (75.86%), sparfloxacìn (72.41%), chloramphenicol (68.97%), streptomycin (65.52%), perfloxacin (56.90%), tarìvid (51.72%), gentamycin (48.28%), ciprofloxacin (48.27%).While thè Gram positive bacteria also exhibited resistance to ampiclox ( 69.12%), septrìn (42.65%), erythromycìn (33.82%), streptomycin (14.71%), gentamycin (11.76%), rocephin (07.35%), zinnacef (02.94%), ciprofloxacin (01.47%). Multi-drug resistance (MDR) to three or more antimicrobials was observed in some of thè isolates. This study revealed high prevalence of MDR bacteria in goat milk that can contrìbute to thè global antibiotic resistance menace through primary or secondary infections assocìated with husbandry, milking and consumption of improperly pasteurized goat milk